ISLAMIC SOCIETY OF BUTON (Historical and Cultural Analysis Study on Buton Islamic Society) - Hasan, Hidayat (Jurnal Kawasan Sejarah, 2023)
Buton in a historical perspective is a sultanate located in Southeast Sulawesi. Geographically, Buton is flanked by the East Nusa Tenggara Folres Sea and the Banda Sea which makes this area a transit area for ships from east to west and from west to east. This research is a qualitative research using historical method approach. This study aims to describe and understand the Muslim community of Buton both from the history, culture and economy of the Muslim community of Buton. In this study it was found that the arrival of Islam in Buton in the mid-16th century AD, had a major influence in the formation of the culture of the local community. Where the arrival of Islam did not directly shake and even erase the traditions of the Buton people, but Islam that came to the Butonese region with hasul entered and influenced culture, in other terms, there was acculturation between the culture or traditions of the Buton people and Islamic teachings. then the strategic geographical location makes this area a transit area for merchant ships, so that the process of Islamization can occur very easily.